Performance Comparison of Conventional Membrane Bioreactor and Moving Bed Membrane Bioreactor for the Treatment of Synthetic Textile Wastewater - Soysaloglu, Ayberk; Takatas, Betul; Erkan, Hanife Sari; Caglak, Abdulkadir; Engin, Guleda Onkal (Mehmet Sinan Bilgili, 2020)
There is growing attention towards moving bed-membrane bioreactor (MB-MBR) technology due to their several advantages, such as improved MBR performance, reduced suspended solids (SS) concentrations, lower membrane fouling propensity and higher membrane flux. In MB-MBR technology, biofilm reactor with bio-carriers and membrane filtration are combined. In the present study, conventional MBR and MB-MBR were investigated for synthetic textile wastewater treatment in terms of chemical oxygen demand (COD) and color removal rates. For this purpose, MBR was operated without bio-carriers for about three months in order to determine the removal efficiencies and membrane fouling propensity. After completion, bio-carriers were added to be 20% of the total reactor volume and MBR was operated with bio-carriers for additional two months. As expected, the transmembrane pressure (TMP) in MB-MBR reduced approximately by half compared to conventional MBR. On the other hand, similar COD removal efficiencies (about 96%) were achieved in both operations, while higher color removal efficiencies were found in MB-MBR. The obtained results show that the MB-MBR improves reactor performance in terms of color removal and TMP.
Keywords: Textile wastewater; membrane bioreactor; moving bed membrane bioreactor; bio-carrier; Engineering; Environmental Sciences & Ecology